Efektivitas Pemberian Saluri (Satu Telur Satu Hari) Terhadap Tinggi Badan Pada Balita Stunting Di Puskesmas Pakuhaji Kabupaten Tangerang Banten Tahun 2022: The Effectiveness of Providing Saluri (One Egg a Day) Against Height in Stunted Toddlers at the Pakuhaji Health Center, Tangerang Regency, Banten in 2022 - Sartikah (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Stunting is one of the most common child health problems in the world. Eggs contain essential amino acids that stimulate muscle protein synthesis. The Pakuhaji Community Health Center, Tangerang Banten Regency, obtained quite high data on stunting toddlers, namely in 2021 there were 162. The Health Center is trying to provide animal food in the form of giving One Egg One Day (Saluri) in October 2022. Methods: Quasy experiment with the one-group pretest-posttest design method. The sample was 39 toddlers who experienced stunting in October 2022 using a purposive sampling technique. Intervention giving one item a day for 3 months. Bivariate analysis using the Wilcoxon test. Results: The results of the univariate study of stunting toddlers' height before the administration of saluri averaged = 74,81 cm after the administration of saluri averaged = 79,00 cm. Bivariate research results with p = 0,000. Discussion: Giving saluri (one egg a day) is effective for height in stunting toddlers. It is hoped that stunted toddler mothers can take good care of their toddlers and pay attention to their intake of foods that contain high animal protein, one of which is by giving one egg a day routinely and obediently in order to increase bone growth and toddler brain development so that stunting can be overcome.